If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15.6 + -3x = 1.5 Solving -15.6 + -3x = 1.5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15.6' to each side of the equation. -15.6 + 15.6 + -3x = 1.5 + 15.6 Combine like terms: -15.6 + 15.6 = 0.0 0.0 + -3x = 1.5 + 15.6 -3x = 1.5 + 15.6 Combine like terms: 1.5 + 15.6 = 17.1 -3x = 17.1 Divide each side by '-3'. x = -5.7 Simplifying x = -5.7
| 5b^2-47b+56=0 | | 2b^2+21+17b= | | 8x*x=414 | | 2x+5=68-7x | | 5x+4=7x-16 | | -6+6j=5j | | -(7)y-3=-31 | | 6(x+3)=27 | | 16m^2-88m+40=0 | | -31-4x=-55(1+5x) | | 16t^2=323 | | 17-z=13 | | 6p=208 | | 16t^2=223 | | 9[2-2x]=3x+2 | | 3y+20= | | (3x+10)=5x | | 15+7x-2x^2= | | 10x^3+12x^2+2x= | | 11x^2+x^3=0 | | 16t^2=338 | | 2x-45+1x+30=180 | | 2x^2+7x+15= | | 8n-7(n-8)=32+5n | | -10n+151=-589 | | 5b+14=-2(2-4b) | | (4h-2)=2(h+3) | | 8(v-8)=-8v-16 | | 44x-29=37x-15 | | 1-5x+3x+4=-3(x+8)+2(6x-2) | | 3+6n-7n=0 | | 2n+6=-20 |